The Impact of Halal Product Exports on Indonesia’s Economic Growth, 2020–2024 - Aulia Rahmi Ma’rifah; Silvia Vitari Anam; Maulana Syarif Hidayatullah (Gudang Jurnal Multidisiplin Ilmu, 2026)
This study examines the effect of export value on Indonesia’s economic growth during the 2020–2024 period. The purpose of the research is to determine whether export performance contributes to the increase of national economic growth in both the short and long term. The research applies a quantitative design using secondary time series data obtained from official institutions, including export data from the Ministry of Trade of the Republic of Indonesia and economic growth data from the Central Statistics Agency. The analysis technique employed is the Vector Error Correction Model, which identifies short-run and long-run relationships between variables. The results show that in the short run, export value has a positive and significant influence on economic growth, while in the long run, it shows a positive but insignificant relationship.